The gut microbiota metabolite trimethylamine N-oxide promotes cardiac hypertrophy by activating the autophagic degradation of SERCA2a - Dongyu Lei; Yi Liu; Yuan Liu; Yujie Jiang; Yuyan Lei; Feilong Zhao; Wenqun Li; Zhonghua Ouyang; Lulu Chen; Siyuan Tang; Dongsheng Ouyang; Xiaohui Li; et al. (Communications Biology)
Abstract Trimethylamine oxide (TMAO) is a newly found intestinal microbiota metabolite. Here, we aimed to explore the effects of TMAO on calcium homeostasis and its implication in cardiac hypertrophy, especially focusing on the regulatory mechanism of TMAO on the key calcium transporter SERCA2a. Echocardiography and histological assessment showed that mice fed with TMAO or Choline for 8 weeks exhibited significant pathological changes of cardiac hypertrophy, which is accompanied by increased plasma levels of TMAO. The results indicated that TMAO could increase the intracellular Ca2+ level, up-regulate the expression of ANP and MYH7, and down-regulate SERCA2a expression, which could be reversed by overexpressing of SERCA2a and BAPTA-AM. Meanwhile, TMAO treatment promotes autophagy in vitro and in vivo. By employing immunofluorescence staining and immunoprecipitation assay, it was found that SERCA2a bound to ATG5 and transported to autophagosomes via the ATG5 complex for degradation under TMAO conditions. Furthermore, either 3MA or siATG5 could ameliorate TMAO-induced cardiomyocyte hypertrophy and SERCA2a degradation. Finally, in vivo intervention showed that 3MA could relieve cardiac hypertrophy and rescue the down-regulation of SERCA2a in TMAO-fed mice. The current study identifies a mechanism in which TMAO promotes cardiac hypertrophy via elevated intracellular Ca2+ levels and enhanced autophagy degradation of SERCA2a.